Conformal ALD of tin-doped indium oxide transparent p-ohmic contacts for micro- and nano-LEDs - Park, Sohyeon; Kim, Taeseok; Park, Sung Hyuk; Kwon, Hee Ryeong; Seo, Sung Jin; Kulkarni, Mandar A.; Ryu, Jung-El; Park, Yongjo; Ryu, Sang-Wan; Kim, Seong Keun; Jang, Ho Won (Royal Society of Chemistry, 2025)
High-performance micro-LEDs require transparent conductive oxides (TCOs) that exhibit excellent electrical and optical properties while remaining compatible with p-GaN. Various TCO deposition methods, including sputtering and e-beam evaporation, have been explored, each with its advantages and challenges. In this study, plasma-enhanced atomic layer deposition (PEALD) was employed to deposit tin-doped indium oxide (ITO) for micro-LED applications. To prevent plasma-induced damage, a bilayer structure was developed with a thin ALD indium oxide buffer layer beneath the PEALD ITO. The resulting ITO film, with a stoichiometry of In1.82Sn0.18O3 and a thickness of similar to 80 nm, exhibited a smooth surface (RMS roughness 0.49 nm), high optical transparency, and excellent conductivity. Post-deposition rapid thermal annealing promoted partial diffusion of the interfacial oxide layer into the ITO and p-GaN, and reduced hydrogen-related defect complexes located near the p-GaN interface. The optimized ITO layer was integrated into micro-LEDs of various sizes (150 x 150 mu m2 to 20 x 20 mu m2), demonstrating uniform electrical performance and low reverse leakage currents of 10-9 A. Long-term stability is confirmed through a constant voltage stress (CVS) conducted at 3.2 V for 76.5 hours. The conformal deposition capability of ALD enables precise and uniform coatings, highlighting its transformative potential in advancing TCO technologies for next-generation optoelectronic devices and high-efficiency displays.